Letwin, Bessie (audio interview #1 of 4) - Letwin, Bessie (b. - d. 5/19/1987); Bright, Susie, interviewer
INTERVIEW DESCRIPTION - This is the first interview of four interviews with Bessie Letwin conducted in her home in Westwood for as part of a student project in a women's oral history class at CSULB. Although Letwin was frank and honest, her unprepossessing manner meant that she did not speak at length on any particular subject. Letwin and the interviewer had known eachother for several years and there references to close friends and relatives are not fully explained. Note: it is sometimes difficult to understand Letwin because of her thick accent. TOPICS - youth in Russia; family background; family history; socioeconomic status; family life; religion; gender roles; commerce in Russian village; anti-Semitism and pogroms; conditions in czarist Russia; education; Jewish culture and values; childhood; household chores; housing and living conditions; and social activities; NOTE: it is sometimes difficult to understand Letwin because of her thick accent;family socioeconomic status in Russia; anti-Semitism; relations with gentiles; religion; family life; family history; clothing styles; health care in Russia; puberty and menstruation; early work experiences; wages and hours; educational aspirations; and schooling and education; Note: it is sometimes difficult to understand Letwin because of her thick accent; 1978-10